Diagnóstico de las microempresas artesanales del cantón Bolívar por actividad en relación al posicionamiento competitivo - Avellán Bailón, Eira María (2016)
This paper aims to diagnose craft microenterprises in the canton Bolivar activity in relation to the competitive position because these are not any investigation to determine how many and which craft microenterprises are in the canton Bolivar. The research was economic development and it was carried through instruments for data collection and field research, the descriptive, analytical, inductive and deductive methods, whose methodology was mixed type, the same who answered the qualitative character and facilitates the use of development features information and quantitative because the numerical values, accessing the analysis, compression and processing of information were handled. The tools used to determine the positioning of them were the questionnaire through a survey and technique of statistics that allow to draw conclusions of the study population and consumers, the focus group and parent competitive profile that allowed us to establish what of these enterprises had more recognition in the market having concluded that there are 946 craft microenterprises in the canton divided into 53 craft activities among which stands out the Chefs. Defining the competitive position of artisanal micro corresponds to the category of Cevicheria and Picantería highlighting its advantages over the competition. He thus allowing the implementation of improvement actions through a proposal will contribute to a better socio-economic performance of artisanal micro-enterprise activity increased incidence in the canton Bolivar.